Ligand-lytic peptides for specific targeting of Leishmania major and Trypanosoma cruzi parasites - Iniguez, Eva; Rodriguez, Felipe; Husseneder, Claudia; Foil, Lane; Maldonado, Rosa A. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionLeishmaniasis and Chagas disease are major human neglected diseases, affecting an estimate of 12 and 6 to 8 million people worldwide, respectively. Current treatments for both diseases are highly toxic for the vertebrate host and lack specificity for the parasites, highlighting the need for the discovery of new therapies against these diseases. In this study, we tested the use of the lytic peptide Hecate and a Ligand-Hecate construct that incorporates a ligand to bind the lytic peptide to protozoa membranes and screened them for protozoacidal activity.MethodsWe first screened parasite survival of luciferase expressing Leishmania major promastigotes and Trypanosoma cruzi epimastigotes in the presence of Hecate or Ligand-Hecate, and after 12, 48 and 96 h by measuring the parasite luciferase activity. In addition, High-Content Imaging Assay was used to evaluate the proliferation of intracellular L. major amastigotes propagated inside murine macrophages after treatment with Hecate or Ligand-Hecate.ResultsThe lowest half maximal effective concentration observed after 48 h of incubation with Hecate and Ligand-Hecate was lower against L. major promastigotes than T. cruzi epimastigotes. Ligand-Hecate treatment significantly reduced infection rate of macrophages L. major amastigotes compared to the non-treated vehicle control; while treatment with Hecate was significant only at higher drug concentrations. Importantly, no significant cytotoxicity was observed when screened against intraperitoneal murine macrophages for either Hecate or Ligand-Hecate treatments.DiscussionOur results indicate that ligand-lytic peptide complexes are potential targets for therapeutic drugs that can selectively kill both extracellular and intracellular protozoa parasites stages with no significant toxicity to host cells.